Control of settlement and volume loss induced by tunneling under recently reclaimed land - A.K.L. Kwong; C.C.W. Ng; A. Schwob (Underground Space, 2019)
The proposed Tuen Mun–Chek Lap Kok Link (TM-CLKL) project comprises a 9-km-long dual two-lane carriageway between Tuen Mun and North Lantau, Hong Kong. Construction of the two tunnels at the Northern Landfall Fall was carried out by two TBMs: the northbound is referred to as ML03 and has an excavated diameter of 17.63 m, and the southbound is referred to as ML02 and has an excavated diameter of 14.00 m. The use of TBMs minimized the amount of dredging and removal of soft marine deposits, resulting in less impact to the environment within and near the work site of the project. Ground treatment in the form of deep vibro-compaction was carried out at the sand fill and band drains installed in the marine deposit. A surcharge was also added above the final formation level to limit the residual settlement and differential settlement of the reclaimed land to less than 500 mm and 1 in 300, respectively, for a design life of 50 years. Finite element analyses were performed to predict the settlement trough under different confinement pressures along the tunnel alignment. Extensive monitoring of the ground movement was carried out during the driving of the two TBMs to ensure that the design confinement pressure of the slurry would not cause excessive settlement, heave, or blow out at the shallow tunnel sections or different facilities along the tunnel alignment. The monitoring data was then used to back-calculate the percentage of volume loss, which is a key index describing the behavior of the ground during excavation. The monitoring data showed that the measured settlement and back-calculated volume loss were much lower than the predicted values. Keywords: TBM excavation, Settlement trough, Volume loss, Ground treatment, Confinement pressure